Le Giulietta e Romeo de Riccardo Zandonai : une création nationaliste en ordre de marche - Emmanuelle Bousquet (Revue LISA)
This article analyses Riccardo Zandonai’s Giulietta e Romeo as a reading of Shakespeare’s tragedy through the double perspective of the eyes of the composer, immersed in the European literary and musical tradition, and those of the public and of the critics in the historical context of widespread nationalism and rising fascism. If nothing in the opera hints at the antagonistic forces at work, the paratext, letters and newspaper articles, provides significant details. If the composer seeks his Italian audience’s approval by referring to the medieval Italian sources of the story and not to Shakespeare’s play, this choice indirectly links him in a roundabout way to the European literary and musical tradition. If he then refuses the modernism of the avant-garde, he will not manage to prevent his opera from being interpreted as a nationalistic work by the fascist state, as, significantly, his opera was first performed in 1922, the year of Mussolini’s March on Rome and seizure of power.